2017
DOI: 10.1093/jme/tjw239
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of Essential Oil From the Leaves ofCroton argyrophyllus(Euphorbiaceae) onAedes aegypti(Diptera: Culicidae) andMus musculus(Rodentia: Muridae)

Abstract: Plant-derived essential oils can be used as insecticides for vector control. However, to establish their safety, it is necessary to perform toxicological studies. Herein, we evaluated the chemical composition and insecticidal activity of the essential oil from the leaves of Croton argyrophyllus on the third- and fourth-instar larvae and adult Aedes aegypti (L., 1762). We also evaluated the acute toxicity of the essential oil in adult female Mus musculus. The lethal concentration 50 (LC50) and 90 (LC90) of C. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 26 publications
3
22
1
1
Order By: Relevance
“…The chemical composition of oils from C. argyrophyllus has been investigated and has been revealed that chemotypes containing main constituents like bicyclogermacrene, ( E )‐caryophyllene and spathulenol are among the most widely known [9,21–24] . The composition of the chemotype that is presented in this paper, with bicyclogermacrene, ( Z )‐caryophyllene, germacrene B and epi ‐longipinanol as the main constituents, is different from those previously registered in the literature.…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…The chemical composition of oils from C. argyrophyllus has been investigated and has been revealed that chemotypes containing main constituents like bicyclogermacrene, ( E )‐caryophyllene and spathulenol are among the most widely known [9,21–24] . The composition of the chemotype that is presented in this paper, with bicyclogermacrene, ( Z )‐caryophyllene, germacrene B and epi ‐longipinanol as the main constituents, is different from those previously registered in the literature.…”
Section: Resultsmentioning
confidence: 57%
“…The chemical composition of oils from C. argyrophyllus has been investigated and has been revealed that chemotypes containing main constituents like bicyclogermacrene, (E)-caryophyllene and spathulenol are among the most widely known. [9,[21][22][23][24] The composition of the chemotype that is presented in this paper, with bicyclogermacrene, (Z)-caryophyllene, germacrene B and epi-longipinanol as the main constituents, is different from those previously registered in the literature. This variation in the composition in relation to previous studies, may be due to several factors such as the specific location of where the plant was collected, vegetative cycle, botanical origin, climate factors.…”
Section: Composition Of the Essential Oilsmentioning
confidence: 98%
See 3 more Smart Citations